CYBER SECURITY AND TOURISM: BIBLIOMETRIC ANALYSIS - Kovačić, Matija; Čičin-Šain, Marko; Milojica, Vedran (Journal of process management and new technologies, 2022)
The topic of cyber security in tourism is of particular importance since tourists in foreign countries are one of the most vulnerable groups due to a lack of knowledge of languages, laws, etc. With the increase in the number of technologies that enable interactivity, contactless payments, i.e., informative content for tourists, risks for the security of tourists' data as well as risks related to the theft of data on tourists' bank cards are emerging. In order to identify the current knowledge, i.e., the current situation in the context of research on cyber security in tourism, a bibliometric analysis was conducted, which indicated that an insufficient number of authors research cyber security and that there is not a sufficient number of studies that would analyze the mechanisms and measures of increasing cyber security in tourism. The importance of researching cyber security in tourism is based on the fact that tourism is a particularly vulnerable and sensitive branch of the economy to risks that affect tourists as such, and that it can depend on the reputation of the country, institutions, or hotels. The bibliometric analysis conducted in this paper is significant for future researchers considering that it can serve as a basis for researchers' focus on specific areas of cyber security.
Keywords: cyber security; tourism; risk; bibliometric analysis